Creative acrylics : a step-by-step beginner's guide to creating with paint & mediums - Co Chua, Carla (Quarry, 2022)
"Creative Acrylics features the best beginner techniques for painting with acrylics, with lessons on painting vibrant florals, animals, landscapes, and still lifes and skill-building projects on a variety of surfaces"--